Негоже лилиям прясть: [романы] / [художник Ю. Ф. Копылов] - Дрюон Морис (Славянка, 1992)
Экземпляры: Пф (1993) / Инвентарный номер: 23707 / Цена: / Авт.знак: Д 78 / ГРНТИ: 17.82.31 / ББК: 84(4Фра)6-44